O Cinema como mediador na Educação para a Cultura Visual - COSTA, Adriane Camilo (2009)
This study, still in course, investigates the magnifying of the joint possibilities, information and interaction of students with the world of the visual culture and its multiple forms of expression, having the cinema as orienting axle. In these terms, part in comment of the mental picture construction favored by the visuality that the cinema provides, questioning how this construction is understood by children with age between 8 and 10 years. The search was developed into two stages, with two groups of children, each group with numbers distincts of components. The first group was formed with twenty five children, and the second one was formed with nine of these children. The work with the first group approached, in dynamics and quantity of students , whith the regular classrooms; while the work with the second group has permited more approximation of the assimilation process and knowledge building. While the children had interacted with the information of the histories from the films and built images, drawing working with clay and another ways, they exercised the observation, the imagination and the memory. The kids represented the relations established among the sensed into the film with the already acquainted for them, with the elaboration way of imaginary. This Project confirms how the importance of the movie can assume in the construction of the knowledge and the esthetic experience among the children between eight and ten years old.